Detection of quadrupolar nuclei by ultrafast 2D NMR: exploring the case of deuterated analytes aligned in chiral oriented solvents. Issue 10 (22nd December 2015) - Lesot, Philippe; Berdagué, Philippe; Giraudeau, Patrick
Abstract : Anisotropic 2 H ultrafast (ADUF) 2D NMR spectroscopy for studying deuterated analytes dissolved in chiral liquid crystals is investigated and its analytical possibilities are evaluated. Abstract : Anisotropic 2 H ultrafast (ADUF) 2D NMR spectroscopy for studying analytes dissolved in chiral liquid crystals (CLC) is investigated for the first time and the analytical possibilities of this method are evaluated. We demonstrate that these unconventional sub-second 2D experiments are compatible with the basic gradient units (40–60 G cm −1 ) that are implemented in routine spectrometers and allow the recording of 2 H signals of weakly aligned deuterated solutes in sub-second experimental times.